Circulating plasma xanthine oxidase contributes to vascular dysfunction in hypercholesterolemic rabbits. - White, C R (1996)
Reactive oxygen species play a central role in vascular inflammation and atherogenesis, with enhanced superoxide (O2.-) production contributing significantly to impairment of nitric oxide (.NO)-dependent relaxation of vessels from cholesterol-fed rabbits. We investigated potential sources of O2.- production, which contribute to this loss of endothelium-dependent vascular responses. The vasorelaxation elicited by acetylcholine (ACh) in phenylephrine-contracted, aortic ring segments was impaired by cholesterol feeding. Pretreatment of aortic vessels with either heparin, which competes with xanthine oxidase (XO) for binding to sulfated glycosaminoglycans, or the XO inhibitor allopurinol resulted in a partial restoration (36-40% at 1 muM ACh) of ACh-dependent relaxation. Furthermore, O2.(-)-dependent lucigenin chemiluminescence, measured in intact ring segments from hypercholesterolemic rabbits, was decreased by addition of heparin, allopurinol or a chimeric, heparin-binding superoxide dismutase. XO activity was elevated more than two-fold in plasma of hypercholesterolemic rabbits. Incubation of vascular rings from rabbits on a normal diet with purified XO (10 milliunits/ml) also impaired .NO-dependent relaxation but only in the presence of purine substrate. As with vessels from hypercholesterolemic rabbits, this effect was prevented by heparin and allopurinol treatment. We hypothesize that increases in plasma cholesterol induce the release of XO into the circulation, where it binds to endothelial cell glycosaminoglycans. Only in hypercholesterolemic vessels is sufficient substrate available to sustain the production of O2.- and impair NO-dependent vasorelaxation. Chronically, the continued production of peroxynitrite, (ONOO-) which the simultaneous generation of NO and O2.- implies, may irreversibly impair vessel function.